Buddha's Cārikā after His Enlightenment - Shakya, Basanta Raj (Historical Journal, 2024)
The Buddha’s of cārikā refers to his travels from place to place, particularly to spread the Dhamma teachings aimed at liberating all sentient beings from suffering. This movement begins with the first sermon at Mr̥gadāvana and continues until the stage of Mahāparinirvāṇa at Kusinagar. This 45-year journey across Jambudvipa, or the Indian subcontinent, was one of the most significant changes in the philosophical world. This paper aims to explore the major incidents of the Buddha's movement in spreading the Dhamma around the Indian subcontinent during 563 BC. It also addresses the formation of the Bhikkhu Saṅgha and Bhikkhuni Saṅgha, as well as the tradition of vassāvāsa and the involvement of laypeople from diverse backgrounds during the Buddha's time. Research methods include descriptive techniques that reference both original and secondary sources. This research paper provides insight into the 45 years of spreading the Buddha's teachings and the establishment of his tradition after enlightenment.